2016
DOI: 10.37341/jkkt.v1i2.83
|View full text |Cite
|
Sign up to set email alerts
|

Bentuk Dan Derajat Luka Perineum Ibu Nifas Di Wilayah Kabupaten Klaten

Abstract: Perineum Laceration Type, Perineum Laceration Level, Post PartumMother. The aim of this research was to know the descriptive of the type and the level of perineum laceration on post partum mother at Klaten. This research was descriptive design. The data were analyzed using descriptive statistics. The respondents were 84 post partum mothers who experienced perineum laceration but without complication. The result showed the majority of perineum laceration type was rupture (86.9 %) and the majority of perineum la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…The experience of pain felt by the postpartum mother will depend on the degree of perineum wound experienced. Previous research [2] showed that of the 59 respondents who experienced laceration complained of mild pain 66.1 %, moderate pain 23.7 %, and severe pain 6 %, while based on other research [12] wrote that 18 respondents who underwent an episiotomy as 13 respondents (72.2%) severe pain, as after intervention and evaluation, there was a significant difference between the two groups in perineum pain with (P=0.004, P<0.001), and in the results of the study, article 5 showed there was a decrease in perineum pain between before and after, which was 1.0 where before the aroma struck lavender the average value was 3.2 and the average value after the aromatherapy lavender was 2.2. The normality test obtained abnormal data distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experience of pain felt by the postpartum mother will depend on the degree of perineum wound experienced. Previous research [2] showed that of the 59 respondents who experienced laceration complained of mild pain 66.1 %, moderate pain 23.7 %, and severe pain 6 %, while based on other research [12] wrote that 18 respondents who underwent an episiotomy as 13 respondents (72.2%) severe pain, as after intervention and evaluation, there was a significant difference between the two groups in perineum pain with (P=0.004, P<0.001), and in the results of the study, article 5 showed there was a decrease in perineum pain between before and after, which was 1.0 where before the aroma struck lavender the average value was 3.2 and the average value after the aromatherapy lavender was 2.2. The normality test obtained abnormal data distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Pain also can make mothers sit comfortably, which can have an adverse effect on the mother's desire to breastfeed (9%). Perineum pain can affect women's well-being physically, psychologically, and socially [2] Treatment of perineum pain exists pharmacologically and non-pharmacologically. The use of pharmacological methods is a pain killer using chemical drugs by administering analgesics and anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Tentu saja semakin dalam dan lebar luka perineum akan semakin menyebabkan nyeri. Bidan sebagai salah satu tenaga kesehatan yang bertugas menolong persalinan diharapkan mampu meminimalkan bahkan mencegah supaya ibu bersalin tidak mengalami luka perineum sehingga saat periode nifas, ibu tidak perlu merasakan nyeri luka perineum (Mulati, 2016).…”
Section: Pendahuluanunclassified
“…When approaching the time of delivery in the third trimester of pregnancy, pregnant women experience anxiety about the stigma that giving birth will be painful and injure the perineum (Sri Mulati, 2016). Injury to the birth canal that can occur during the birth of a baby with or without the use of a device is called a perineal rupture.…”
Section: Introductionmentioning
confidence: 99%